Prevalence and Molecular Characterisation of Vancomycin Resistant Enterococci (Vre) Isolated from Beef - Fifadara, Nimita Hasmukh (2001)
The present study was to isolate VRE from imported beef Tn Malaysia, beef is the major consuming animal originated food and most of the beef is imported from those countries where the use of antibiotics in the feed of animals as a growth promoter was a common practice and was licensed. Out of 150 samples, 17 (11.3%) were positive for VRE. Sixty-seven (67) VRE were isolated from frozen imported beef (48) and burgers (19). The species identified were E. faeclum (35), E. faecalls (22), E. faecalls asaccharolytic variant (3), E. pseudoavlum (3), E. gal/marum (2), E. maldoratus (1) and E. avlum (l). Various plating media and broths were evaluated for the isolation of VRE. Azide Dextrose broth (ADB) with vancomycin concentration of 50 µg/ml for 48 h enrichment and plating on Slanetz and Bartley agar (SBA) with vancomycin concentration of 50 µg/ml was concluded best for isolation of VRE. In the present study antibiotic resistance patterns and the rates of resistance of 67 isolates were evaluated. Itwas observed that all the isolates were multiple resistant and resistant to ten of the sixteen antibiotics tested. All isolates were 100% resistant to streptomycin, vancomycin and teicoplanin. Other isolates were resistant between 94% to 97% to other eight antibiotics. Penicillin, ampicil1in and chloremphenicol showed the least resistance namely, 26.8, 38.8 and 58.2%, respectively. Hemolytic activity on horse blood agar showed that 29 out of 67 isolates (43.3%) were j3-hemolytic indicating to have potency to be pathogenic. The plasmid profiling revealed that 39 (58.2%) out of 67 bear plasmids of the range 1.0 to 35.8 MDa. Using specific PCR, vanA gene was detected among 65 of 67 isolates (97%) which is considered to make these isolates resistant to vancomycin. The molecular epidemiology of E. faecium and E. faecalis using RAPD-PCR technique showed the difference in the genetic relatedness of the strains isolated from frozen imported beef and beef burgers. It showed the genetic relatedness in terms of % similarity from the dendrogram prepared between all the strains taken into study_ RAPD-PCR gave high discriminating results between all the strains. The work clearly reveals that beef can be a vehicle for VRE in Malaysia. The need for intervention to control or eliminate antibiotic resistant Enlerococcu') from foods of animal origin has been made clearer by the results presented in this study.